Factors contributing to fraudulent claims in medical insurance: perspective of public at Gombak, Selangor / Farah Najwa Abdul Aziz - Abdul Aziz, Farah Najwa (Faculty of Business and Management, 2011)
It cannot be denial, now a day’s fraud insurance claims in Malaysia are become serious, which causing insurance companies have lost of hundreds of millions of ringgit. Especially for the medical insurance, where people are willing to chop their finger off, medical ailments exaggerated and even death faked for the purpose of fraud claims. Since this problem become increasing each year, insurance companies or insurance provider must found the way how to handle this before it become worse in the future. Insurance companies or insurance provider should understand clearly the current situation by identify the factors that contributing to the fraudulent claims in medical insurance. By this understanding, insurance companies and insurance provider will get an idea or ways on how to reducing fraud claims in the future. Therefore, this research is conduct to study the factors that contributing to fraudulent claims in medical insurance.